Information Technology and Innovation Trends in Organizations ItAIS: The Italian Association for Information Systems - D'Atri, Alessandro; Ferrara, Maria; George, Joey F.; Spagnoletti, Paolo; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2011)
The book examines a wide range of issues that characterize the current IT based innovation trends in organisations. It contains a collection of research papers focusing on themes of growing interest in the field of Information System, Organization Studies, and Management. The book offers a multi-disciplinary view on Information Systems aiming to disseminate academic knowledge. It might be particularly relevant to IT practitioners such as information systems managers, business managers and IT consultants. The volume is divided into XIV sections, each one focusing on a specific theme. A preface written by Joey George, president of the Association for Information Systems opens the text. The content of each section is based on a selection of the best papers (original double blind peer reviewed contributions) presented at the annual conference of the Italian chapter of AIS, which has been held in Naples, Italy, on October 2010.
Organizational Change and Impact of ICT -- E-Services in Public and Private Sectors -- IS Development and Design Methodologies -- New Ways to Work and Interact via Internet -- Business Intelligence Systems Their Strategic Role and Organizational Impacts -- IS Quality, Metrics and Impact -- Information and Knowledge Management -- Accounting Management and Information Systems -- Information Systems, Innovation Transfer, and New Business Models -- ICT in Individual and Organizational Creativity Development -- IS, IT and Security -- Enterprise Systems Adoption -- ICT-IS as Enabling Technologies for the Development of Small and Medium Size Enterprises -- Human-Computer Interaction.
Keywords: Economics; Information Systems; Business planning; Management information systems; Economics/Management Science; Business Information Systems; Innovation/Technology Management; Management of Computing and Information Systems; e-Commerce/e-business.; Organization/Planning.